2013
DOI: 10.1007/s11274-013-1522-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic analysis of dominant microbial populations in aged refuse

Abstract: The phylogenetic analysis of dominant microbial populations in 8-year-old refuse samples was done in terms of the whole Bacterial and Archaeal domains. The results indicated that the Bacterial 16S rRNA genes sequences from the aged refuse were largely affiliated with the genus Bacillus, and that more than 60 % of the Archaeal sequences were closely related to the methanogenic archaeon. Some inferentially identified extremophilic organisms, particularly alkaliphiles and/or halophiles, were noted to be present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This landfill depth was dominated by phyla Firmicutes, Epsilonbacteraeota, Proteobacteria, and Bacteroidetes in both the 14-and 36-year-old landfills. Several studies have also indicated the dominant presence of Firmicutes, Proteobacteria, and Bacteroidetes in different maturing landfills (Gomez et al, 2011;He et al, 2014;Song et al, 2015;Thakur et al, 2020;Wang et al, 2017;Xu et al, 2017). These mixotrophic phyla are among the most metabolically diverse bacterial groups that metabolize a variety of organic and inorganic substrates (Aislabie & Deslippe, 2013;Vetrovsky, Steffen, & Baldrian, 2014;Ximenes, Cowie, & Barlaz, 2018), as such are functionally key in the degradation of the heterogeneous MSW in landfills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This landfill depth was dominated by phyla Firmicutes, Epsilonbacteraeota, Proteobacteria, and Bacteroidetes in both the 14-and 36-year-old landfills. Several studies have also indicated the dominant presence of Firmicutes, Proteobacteria, and Bacteroidetes in different maturing landfills (Gomez et al, 2011;He et al, 2014;Song et al, 2015;Thakur et al, 2020;Wang et al, 2017;Xu et al, 2017). These mixotrophic phyla are among the most metabolically diverse bacterial groups that metabolize a variety of organic and inorganic substrates (Aislabie & Deslippe, 2013;Vetrovsky, Steffen, & Baldrian, 2014;Ximenes, Cowie, & Barlaz, 2018), as such are functionally key in the degradation of the heterogeneous MSW in landfills.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant bacterial classes in the 14‐year‐old landfill were Clostridia and Bacilli , which are the most proliferate classes of phylum Firmicutes found in MSW landfills (Huang, Zhou, Zhu, & Qu, 2004; He et al, 2014; Mwaikono et al, 2016; Song et al, 2015; Xu et al, 2017). There was a positive correlation of these bacterial classes with moisture, TN, TC, S, and P in the 14‐year‐old landfill as revealed by canonical correspondence analysis, suggesting that they thrive under high moisture content and nutrient concentrations evident in the 14‐year‐old landfill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stabilised or essentially stabilised refuse is termed ‘aged refuse’ in the present study. It is estimated that at least 200 million tonnes of such aged refuse are available in China alone, and at least 10 times that much is buried worldwide (He et al, 2014; Zhao et al, 2007). The recycling of aged refuse has been gaining ever-growing attention and numerous recycling pathways have been tried in the past decade (Lou et al, 2015; Prechthai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work that discussed the ammonia removal mechanism of aged refuse media mainly focused on biological transformation processes, such as nitrification, denitrification and anaerobic ammonium oxidation (Chen et al, 2009; Han et al, 2013; He et al, 2014; Long et al, 2009; Wang et al, 2014). In principle, the adsorption, desorption and ion exchange are intertwined with the bioprocesses for the ammonia removal in aged refuse media.…”
Section: Introductionmentioning
confidence: 99%